2014
DOI: 10.1063/1.4862026
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-driven and excitation-dependent recombination rate in blue InGaN/GaN quantum well structures

Abstract: We report on diffusion-driven and excitation-dependent carrier recombination rate in multiple InGaN/GaN quantum wells by using photoluminescence, light-induced absorption, and diffraction techniques. We demonstrate gradually increasing with excitation carrier diffusivity and its correlation with the recombination rate. At low carrier densities, an increase in radiative emission and carrier lifetime was observed due to partial saturation of non-radiative recombination centers. However, at carrier densities abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 25 publications
7
19
0
Order By: Relevance
“…In our case grains are too large ∼1–5 μm to explain such process. Also similar effect of excitation‐enhanced and diffusion‐limited nonradiative recombination was observed in InGaN QWs . As for the given Al‐rich AlGaN heterostructures, the localized carriers exhibit longer lifetimes only at low excitations, while at increased excess carrier density part of electrons and holes become delocalized and can easily reach nonradiative defects.…”
Section: Resultssupporting
confidence: 64%
“…In our case grains are too large ∼1–5 μm to explain such process. Also similar effect of excitation‐enhanced and diffusion‐limited nonradiative recombination was observed in InGaN QWs . As for the given Al‐rich AlGaN heterostructures, the localized carriers exhibit longer lifetimes only at low excitations, while at increased excess carrier density part of electrons and holes become delocalized and can easily reach nonradiative defects.…”
Section: Resultssupporting
confidence: 64%
“…The second emission band had a much shorter decay time and was attributed to the recombination of weakly localised or delocalised carriers that occurs due to the saturation of the localised states. Efficiency droop in c-plane QWs at low temperatures has also been shown previously 39 to correlate with the saturation of localised states, in particular, those responsible for the localisation of holes 16 leading to the proposal 16,43,44 that saturation of the localised states is a key precursor to the non-radiative losses responsible for efficiency droop. This behaviour is broadly in line with the original suggestion by Hader et al 15 In summary, we have shown that, most importantly, efficiency droop does occur in non-polar QWs as long as the injected carrier density is sufficiently large.…”
mentioning
confidence: 94%
“…[4][5][6] Strong motivation for these studies has been provided by the technological importance of group-III nitride semiconductors as the key materials for light emitters in the green and blue spectral regions. 7 With band gaps of 3.5 eV for GaN and 0.7 eV for InN, 8 InGaN alloys can cover the entire visible spectrum.…”
mentioning
confidence: 99%
“…Progress in nitride growth currently allows producing materials with dislocation densities <10 6 cm −2 , and there is a consensus that it is point defects that cause SRH recombination in such materials. 6,9,10 However, the microscopic origin and mechanism of SRH recombination in nitrides has remained elusive. This is a serious handicap for improving device efficiencies.…”
mentioning
confidence: 99%